Genetic Diversity of the Collection of Far Eastern Actinidia spp. Revealed by RAD Sequencing Technology - Natalia Slobodova; Maria Gladysheva-Azgari; Fedor Sharko; Kristina Petrova; Eugenia Boulygina; Svetlana Tsygankova; Irina Mitrofanova (Plants)
More than ten species of the Actinidia Lindl. genus bear edible fruits rich in biologically active compounds, which are essential and beneficial for human health. The most popular cultivars today are the large-fruited Actinidia species, A. deliciosa and A. chinensis, commonly known as kiwi. However, small-fruited kiwi cultivars are gaining prominence due to their high nutritional value, superior cold resistance, and suitability for temperate climates. In Russia, these are represented by Far Eastern species: A. arguta, A. kolomikta, and A. polygama. Despite increasing consumer interest, Russian Actinidia cultivars remain little studied, with fragmented genetic data available for breeding purposes. Our objective was to analyze the Actinidia collection at the Federal Horticultural Center for Breeding, Agrotechnology, and Nursery and the N.V. Tsitsin Main Botanical Garden (MBG RAS, Moscow), which includes samples from four species, A. kolomikta, A. arguta, A. polygama, A. purpurea, interspecific hybrids, and derived varieties, using RAD sequencing. We assessed the genetic variability of all species, identified population groups within A. kolomikta and A. arguta based on origin, determined ploidy levels across the collection, and identified a set of SNP markers associated with valuable agronomic traits.